Ampliación y Readecuación del Hospital el Salvador de Ubaté (2022)
In this project it was carried out with the aim of proposing an Extension and Readaptation of the Hospital el Salvador de Ubaté, focusing on the municipality of San Diego de Ubaté, developed some strategies, to increase and improve the spaces of the building to intervene, the current infrastructure of the hospital presents some spaces in deterioration affecting the services for the community, so an investigation is carried out to get to the bottom of the specific problems that arise in the intervention area. The urban and architectural analyses that were carried out generated as a result an expansion of new spaces and integrate a new cardio vascular specialty. In the new building, the administrative reorganization, cardio vascular specialty, ICU for older adults and hospital areas for men and women were implemented.